PENGARUH BEBERAPA INDEKS HARGA SAHAM DUNIA DAN INDIKATOR MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN INDONESIA TAHUN 2005 SAMPAI DENGAN 2014 - Harbi, Muhamad; M. Rasuli, M. Rasuli; Wijaya, Errin Yani (Jurnal Tepak Manajemen Bisnis, 2016)
Capital market in Indonesia in its development has shown its place as part of the economic instruments , which is used as a reference by researchers and practitioners in seeing the picture of the Indonesian economy . Empirical data show that from 2008 to the end of 2012 fluctuations in the Indonesian Composite Stock Price Index (IHSG), which tends to increase. It proves that economic indicators several years after the global crisis indicate the symptoms restoration of confidence is increasing. In general, experts agree that the international stock exchanges interlinked with each other . In this case , usually the larger exchanges will affect the smaller exchanges. Since the growth of the Indonesian capital market quite rapidly, it appears that the capital market in Indonesia is also indicated relatively vulnerable to macroeconomic conditions of the world in general. It is necessary to study factors that influences Indonesian Composite Stock Price Index (IHSG). The global stock indices that used in this study are: the Dow Jones index, Nikkei 225 index, Shanghai Composite Index (SSE), UK : FT100, KLCI, STI index, which taken monthly from January 2005 until December 2014. The macroeconomic indicators that used in this study include oil prices, gold prices, and the exchange rate USD / IDR that taken monthly from January 2005 until December 2014. To determine whether a stock index and global economic indicators have a positive or negative effect on IHSG, a tool already used in this study, which is using multiple linear regression analysis. The results of this study indicate that the Dow Jones index, Shanghai index, UK : FT100 index, KLCI index, and STI Index significantly give the positive effect to IHSG, while the Nikkei 225 index variable, world oil prices, gold prices, and the exchange rate USD/IDR giving negative effect to IHSG. Future studies wishing to examine the influence of multiple indices and global economic indicators of the condition of the Indonesian capital market can add a variable index of Asia Pacific countries such as: Hang Seng Index (Hong Kong), Kospi Index (South Korea), BSE index (India) and macroeconomic variables such as: inflation, BI rate, GDP (Gross Domestic Product).